Conceptual metaphors of TIME in translation: The Seasons by Kristijonas Donelaitis - Vaivadaitė-Kaidi, Eglė (Taikomoji kalbotyra, 2014)
This research focuses on conceptual TIME metaphors in Kristijonas Donelaitis’s The Seasons in order to supplement a so far scarce research in Lithuania of conceptual metaphors in translation, as time metaphors constitute fundamental aspects of culture and communication (Lakoff, Turner 1989). The present research aims to 1) analyze conceptual time metaphors in The Seasons and systemize them; 2) determine whether the metaphors are preserved in the translations of The Seasons: into Spanish (Caro Dugo 2013), English (Tempest 1985) and German (Passarge 1999).Text fragments were selected from The Seasons with hyponyms of the time concept which were analyzed based on the methodology of conceptual metaphors. Linguistic aspects of conceptual metaphors were compared with the mentioned translations. All the examples were analyzed based on the methodology of translation of linguistic aspects of conceptual metaphors as specified by Kövecses (2005).The following conceptual time metaphors were found in The Seasons: TIME IS OBJECT, TIME IS VOLUME, TIME IS LIMITED RIGHTS, TIME IS PLANT, TIME IS FOOD, TIME IS FESTIVAL, TIME IS MOVING OBJECT, TIME IS CHARACTER, TIME IS HUMAN, TIME IS ANIMAL.By comparing the linguistic aspects of the conceptual time metaphors in The Seasons by Donelaitis and the way they are rendered across several languages, it was determined that most often the conceptual metaphor in translation is preserved, i.e. the conceptual metaphor as well as its literal and figurative meaning are the same in both the original text and the translation. Only one case was found when the literal meaning and the underlying conceptual metaphors were different in the original and all three translations; however, the figurative meaning is maintained. In some cases the conceptual metaphor and its linguistic expression are different in the original text and the translation. Such cases probably occur due to the fact that the translator chooses a different source domain, which changes the conceptual metaphor and the mappings. Another reason could be concerned with the translator’s decision to distance himself/herself from the original due to linguistic and cultural aspects or text-specific factors.
Keywords: Cognitive Linguistic; Conceptual Metaphor; translation; TIME concept; Kristijonas Donelaitis; The Seasons